HELIСOBACTER PYLORI-ASSOCIATED GASTRIC ULCER DISEASE: CLINICO-IMMUNOLOGI-CAL EFFECTIVENESS OF TREATMENT WITHOUT ANTIBIOTICS - T. A. Smirnova (SPb RAACI, 2014)
Abstract. Most data of Heliсobacter pylori (HP) lifelong persistence in gastric mucosa and the intimate mechanisms of resistance to this infection are based only on phenomenological findings, such as absence or low HP colonization in mice and men spontaneously producing high levels of IL-2. 108 patients suffering from HP-associated gastric ulcer disease were randomly divided into two groups. The I group of patients was cured with standard three or four component methods of therapy included of two antibiotics (usually Klaritromycin and Amoxicillin), proton pomp inhibitors and H2 receptor antagonists. Patients of the second group were treated with the same therapy, but instead of antibiotics they received 0,1 mg rIL-2 - Roncoleukin dissolved in 2 ml 0,9% NaCl into four - six points аround gastric ulcer submucously using gastroscope techniques and 0,4 mg was dissolved in 400 ml 0,9% NaCl with 4 ml 10% human albumin and infused intravenously. This procedure was performed three times with the interval of 72 hours. Immunotherapy results in increase of CD25+, HLA-DR+ and CD16+CD56+ cells levels and the increase of the serum concentrations of IL-1б (3 folds), IL-6 (4 folds) and IFNг (more than 20 folds). One month after the end of treatment it was found that in the group treated with rIL-2 the HP eradication achieved in 95,4% in comparison to 81,5% in control patients. In Roncoleukin treated group ulcer epithelization period was 10,79±0,46 days and in traditionally treated group - 35,23±1,58 days.